Discontinuous transcription of ribosomal DNA in human cells - Smirnov, Evgeny; Trosan, Peter; Cabral, Joao Victor; Studeny, Pavel; Kereïche, Sami; Jirsova, Katerina; Cmarko, Dušan (PloS one, 2020)
Numerous studies show that various genes in all kinds of organisms are transcribed discontinuously, i.e. in short bursts or pulses with periods of inactivity between them. But it remains unclear whether ribosomal DNA (rDNA), represented by multiple copies in every cell, is also expressed in such manner. In this work, we synchronized the pol I activity in the populations of tumour derived as well as normal human cells by cold block and release. Our experiments with 5-fluorouridine (FU) and BrUTP confirmed that the nucleolar transcription can be efficiently and reversibly arrested at +4°C. Then using special software for analysis of the microscopic images, we measured the intensity of transcription signal (incorporated FU) in the nucleoli at different time points after the release. We found that the ribosomal genes in the human cells are transcribed discontinuously with periods ranging from 45 min to 75 min. Our data indicate that the dynamics of rDNA transcription follows the undulating pattern, in which the bursts are alternated by periods of rare transcription events.
Keywords: uridintrifosfát; HeLa Cells; Ribosomes; RNA ribozomální; ribozomální DNA; Kinetics; DNA, Ribosomal; transfekce; Cell Nucleolus; software; Transcription, Genetic; Transfection; lidé; HeLa buňky; Epithelial Cells; Uridine; limbus corneae; Cold Temperature; Uridine Triphosphate; Middle Aged; RNA, Ribosomal; mrtvola; genetická transkripce; Aged; Cadaver; uridin; Software; ribozomy; lidé středního věku; senioři; nízká teplota; buněčné jadérko; epitelové buňky; kinetika; Limbus Corneae; Humans